Om et fjernt forarbejde til Poul Martin Møllers “En dansk Students Eventyr” - Ravn, Kim (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
In the spring of 1820, immediately after his arrival in China, Poul Martin Møller (1794-1838) wrote a prose piece based on Walter Scott’s (1771-1832) historical novel of the Scottish Highlands, “The Lady of the Lake,” of 1810. This work, consisting of eight closely written pages, is Møller’s first attempt at continuous prose and is the beginnings of what would become his literary masterpiece, the unfinished short novel “The Tale of a Danish Student.” Although in many respects Møller’s Scottish effort appears but distantly related to the story of the Danish students, it is possible, with the appropriate detours, to trace the connection between Scott and Møller and to see how the latter transformed the historical point of departure into a psychological portrait of his contemporaries.